2016
DOI: 10.20884/1.anprod.2016.18.2.473
|View full text |Cite
|
Sign up to set email alerts
|

Performance Indices and Physiological Changes in Pearl Guinea Fowls (Numida Meleagris) Supplemented with Molasses through Drinking Water

Abstract: Abstract. The study was aimed at evaluating the performance indices and physiologic changes in pearl guinea fowls (Numida meleagris) supplemented with molasses through drinking water. A total of thirty-two (n=32) day-old pearl guinea fowls raised to 12-week-old were used for the study. The fowls were randomly allocated to two groups (control and experimental) of 16 fowls each, with each having two replicates. Experimental fowls were given 5 mL molasses per litre of drinking water for 8 weeks, while control fow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…These favourable nutritional attributes make S. birrea caffra kernel meal a potential DP and energy source in poultry feeds. Previous studies have shown that Marula nut meal (MNM) has been successfully utilised as a DP source in sheep ( Habibu et al., 2016 ), cattle ( Mdziniso, Dlamini, Khumalo & Mupangwa, 2016 ), broiler chicken feeds ( Mdzinisoet al., 2016 ) and Japanese quail ( Mazizi, Moyo, Erlwanger & Chivandi, 2019 ). Despite the reported successful use of the MNM as a DP source in the feed different livestock and poultry species, its potential has not been evaluated in Guinea fowl.…”
Section: Introductionmentioning
confidence: 99%
“…These favourable nutritional attributes make S. birrea caffra kernel meal a potential DP and energy source in poultry feeds. Previous studies have shown that Marula nut meal (MNM) has been successfully utilised as a DP source in sheep ( Habibu et al., 2016 ), cattle ( Mdziniso, Dlamini, Khumalo & Mupangwa, 2016 ), broiler chicken feeds ( Mdzinisoet al., 2016 ) and Japanese quail ( Mazizi, Moyo, Erlwanger & Chivandi, 2019 ). Despite the reported successful use of the MNM as a DP source in the feed different livestock and poultry species, its potential has not been evaluated in Guinea fowl.…”
Section: Introductionmentioning
confidence: 99%